Early activity after strong sutures helps to tendon healing in a rat tendon rupture model - Chenfei Li; Jian Lu; Tianhao Guo; Xuyang Shi; Meng Fu; Yipeng Yang; Yanqing Zhou; Lingde Kong; Bing Zhang (Scientific Reports)
Abstract The purpose of this study was to investigate the effect of different times return to activity on tendon healing after Double Kessler method suture in rats with Achilles tendon rupture. The left Achilles tendon of 80 10-week-old rats was repaired. The rats were randomly divided into 4 groups: non-fixed group, fixed one week group, fixed two weeks group and fixed three weeks group. In the fourth week, all rats were trained on a treadmill for one hour a day at a speed of 10 m/min. Complications were recorded during the study period and passive ankle motion was measured after the rats were euthanized. The healing and adhesion of tendons were evaluated by anatomy, biomechanics, histology and immunohistochemistry. The earlier return to activity after surgery, the higher the quality of tendon healing and the less adhesion will occur. There was no difference in complication rate among the four groups (P< 0.05). There was one case of tendon re-rupture in the non-fixed group and one case in the fixed one week group. The passive range of motion, biomechanical properties, histological evaluation and immunohistochemical results of the ankle in non-fixed group were better than those in the other three groups, while those in fixed three weeks group were worse than those in the other three groups (P< 0.05). The passive ankle range of motion, count of fibroblasts, biomechanical results, and immunohistochemical results showed no statistic significant difference between the fixed one week group and fixed two weeks group (P> 0.05). Early return to activity with strong sutures is advantageous for tendon injuries. With the advanced of return to activity time, the healing strength of tendon increased and the degree of adhesion decreased four weeks after surgery.